Kemampuan Finansial Mantan Suami Terhadap Kewajiban Menafkahi Pasca Cerai - Shifra Adline bevinda (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The determination of alimony after divorce is a significant issue in the practice of religious courts in Indonesia. This article aims to analyze why the alimony that a husband is obligated to provide to his former wife must be adjusted according to the husband's financial capacity. The research method used is normative juridical with an analytical approach to legislation, the Compilation of Islamic Law, and relevant religious court decisions. The results show that adjusting alimony based on the husband's ability is grounded in the principles of justice and fairness in both Indonesian positive law and Islamic law. Furthermore, the alimony obligations, including maintenance during the iddah period, child support, and mut’ah (compensation), must be fulfilled proportionally so as not to overly burden the husband while still protecting the rights of the former wife and children. In conclusion, aligning alimony with the husband's financial capacity reflects the application of justice principles consistent with the objectives of both Islamic and national law.